EPISTIMOLOGI PERPAJAKAN DALAM PEMIKIRAN AL-MAWARDI - KAZWAINI KAZWAINI (An-Nida', 2017)
The establishment of a state is generally intended to protect and prosper the citizen in economic, politic, social and culture. To actualize citizen prosperity is not only the responsibility of the government but also the citizen.  Generally the government raise the pund by tax. Tax is the citizen tuition for nation based on constitution (that could be forced) without any direct reciprocal servive and could be used to pay public spending. In Islam, the tex is termed al-Kharaj. Al Mawardi an Islamic political and economic expert explain that al- Kharaj is charges to be faid on seized and conquered land by moslem over heathen and governor let somebady to manage as the pay taxes to the goverment.Tax collecting must be fair. Imam al-Mawardi explain that tax rates depends on priests deal by considering. Irrigation  model that used, kind of soil, planted crops, and distance from the market. Indonesia imoslem s majority country. As a good muoslem that obey the god and goverment, they are  double charged. They have to pay taxes and also have to pay zakat. Taxes and Zakat are sources of state income. In Islam, beside of zakat, another funds collecting methode are still allowed. On the other word can be said, zakat is not the only source of state income.